2021
DOI: 10.30892/gtg.34119-630
|View full text |Cite
|
Sign up to set email alerts
|

The Interdependence Between Tourism and Innovation Activity in the Western Borderlands of Russia

Abstract: An intensive movement of people, which is typical in areas with strong tourism industry, is perceived to provide numerous positive externalities with regards to the diversity of cultures, ideas, and knowledge. Border regions act as natural contact zones experiencing the influx of tourists across borders. The borderland is expected to benefit from their geolocation and intensive cross-border cooperation, acting as testing grounds for external innovations. The article iS designed to test the interdependence betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…There is a global trend toward consumer-driven and ecologically friendly innovations in tourism and hospitality that encompass the range of interconnected services and goods packaged into a single quality perception of the destination and local community by a tourist. It is worth noting that both vectors of expanding and contracting research and inventive organizations largely parallel the patterns observed for travel agents and, to a lesser extent, housing facilities, sanatoriums, and resorts ( Gorochnaya, Mikhaylov, Plotnikova, & Mikhaylova, 2021 ).…”
Section: Descriptive and Conceptual Structuresmentioning
confidence: 90%
“…There is a global trend toward consumer-driven and ecologically friendly innovations in tourism and hospitality that encompass the range of interconnected services and goods packaged into a single quality perception of the destination and local community by a tourist. It is worth noting that both vectors of expanding and contracting research and inventive organizations largely parallel the patterns observed for travel agents and, to a lesser extent, housing facilities, sanatoriums, and resorts ( Gorochnaya, Mikhaylov, Plotnikova, & Mikhaylova, 2021 ).…”
Section: Descriptive and Conceptual Structuresmentioning
confidence: 90%
“…Innovation is very critical in building public organizations' credibility and reputation, as people tend to assume that hospitality sector services tend to be less quality-based than private service providers. With service innovation in the hospitality industry, there are substantial opportunities to increase the quality of services offered, boost economic growth, and draw more investors (Gorochnaya et al, 2021;Favoreu et al, 2019;Waheed et al, 2019).…”
Section: Service Innovationmentioning
confidence: 99%
“…The tourism and hospitality sector plays a crucial role in any country's economy (Gorochnaya et al, 2021;Akbari and Monzavi, 2015). The tourism industry is one of the most industrial sectors driving the global economy at the present time (Bazazo and Alananzeh, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Tourism analyses and their relationship with indigenous communities appear to use qualitative methods, as well as secondary analyzes of geographical, economic and ecological evidence introduced since the start of tourism ventures. There are little, often suspect, community benefits from tourism that seem to disapprove of resources and influence in the political-economic process of interaction between the two countries (ÇavuĢoğlu et al, 2020;Gorochnaya et al, 2021;Maaiah and Wouhoush, 2020;Hermann et al, 2020).The environmental effect of tourism is possible, since tourism is always developed utilizing natural resources in vulnerable settings (Zeng and Ryan, 2012). The possible negative and positive impacts of any tourism growth activity on the local ecosystem are associated with (Smeral, 2015).…”
Section: Introductionmentioning
confidence: 99%